Pineapple Stem Extract (Bromelain) as Corrosion Inhibitor for Low Carbon Steel in Ambient Environment - MUSTAFA KAMAL, LUQMAN NUR HAKIM; EMBONG, ZAIDI (Enhanced Knowledge in Sciences and Technology, 2022)
Steel is an iron-based alloy with a carbon content of up to 2% (with a higher carbon content, the material is called cast iron) and is widely used for infrastructure construction. Due to the excessive use of acids, metal corrosion has become a big concern in many industries, infrastructure and public services such as water and sewage supply. Acidic solutions like HCI and H2SO4 are commonly employed in industrial operations for acid pickling, acid descaling and acid cleaning, all of which induce corrosion. The objectives of this study were to characterize the chemical and physical properties of pineapple stem extract (powder form) using FTIR, to compare the morphology for the low carbon steel surface in the presence and without inhibitor using SEM-EDX and lastly to study corrosion inhibition efficiency of pineapple extract (Bromelain) for mild steel in ambient environment using weight loss and Raman Laser spectroscopy. The corrosion inhibition of mild steel in HCl by pineapple stem extract (bromelain) was studied using weight loss and. The inhibition efficiency increases with increase in the extract concentration. The mechanism of chemical adsorption is proposed from the observation of FTIR. Mainly, this thesis discussed about the inhibitive effects of a new corrosion inhibitor as a follow-up to the research for an effective corrosion inhibitor.